CREATION OF INSTITUTIONAL AGRICULTURAL PRODUCTION AND INFRASTRUCTURE FORMATIONS OF THE EUROPEAN TYPE AS THE BASIS OF MULTIDISCIPLINARY DEVELOPMENT OF THE RURAL ECONOMY IN UKRAINE (INNOVATIVE ECONOMY, 2020)
Stelmashchuk A.M. CREATION OF INSTITUTIONAL AGRICULTURAL PRODUCTION AND INFRASTRUCTURE FORMATIONS OF THE EUROPEAN TYPE AS THE BASIS OF MULTIDISCIPLINARY DEVELOPMENT OF THE RURAL ECONOMY IN UKRAINEPurpose. The aim of the article is to substantiate theoretical and methodological provisions and practical proposals for the creation of institutional agricultural production and infrastructure formations of the European type as the basis of multidisciplinary development of the rural economy.Methodology of research. Methodological basis of the research are the scientific methods of cognition, which are based on the system approach to the solution of the tasks. A number of general and special scientific approaches and research methods have been used to achieve the goal and to obtain the results of the study: dialectical; monographic (when working out scientific publications); the method of scientific abstraction (separation from all random, insignificant, penetration into the essence of economic phenomena and processes), an integrated approach (in the study of the effectiveness of various organizational and legal forms of management); the method of analogies and comparisons (in the study of agricultural production and infrastructure formations of the European type); the method of system analysis (when forming conclusions and proposals for the solution of the tasks), and others.Investigating the stated issues, the resolution of the Cabinet of Ministers of Ukraine, laws of Ukraine, normative acts of ministries and departments, information of the Ministry of Agrarian Policy and Food of Ukraine, monographs, scientific articles, information from the Internet, etc., are worked out.Findings. The essence of the basic theoretical positions of the investigated problem is substantiated; the European experience of multidisciplinary development of rural territories is worked out. It is established that the institutional provision of the development of Ukrainian territories is characterized by slowness, unsystematic and fragmentary state measures for the implementation of the tasks of systemic reforms. It is determined that today in Ukraine there are very few sources of alternative policy options, although there is an extremely powerful formal state control over the activities of public administration, while no one really is responsible for the quality of the recommendations on the development and implementation of policies and services. It is proposed to intensify the development of civil society as the basis for expanding European type infrastructural formations and multidisciplinary rural economy development. The expediency of preserving farming and rural lifestyle based on the development of cooperatives has been substantiated.Originality. It is substantiated to create a special self-sufficient interregional (interregional) Centre for Strategic Development of Rural Areas on the basis of a research institution with the formation of a network of regional and local rural development agencies, which will become a coordinating tool for addressing the multifaceted problems of rural areas. There must be functioning self-supporting departments at the Centre: technology transfer; development, expert evaluation and implementation of innovation and investment projects; organization of the labour market, resources and products; consulting and advisory, publishing and information and others. Local rural development agencies are set up at the municipal level to carry out informational, consulting, communication and marketing activities in rural areas.Practical value. The obtained research results will promote the formation of sound agricultural policy, organization of strategic planning of multifunctional development of rural territories; support local self-government in promoting a large-scale dissemination of innovations in the spheres of agrarian business and non-agricultural activities.Key words: rural territories; multidisciplinary development; institutional support; agricultural production and infrastructure formations of the European type.
Keywords: Key words; rural territories; multidisciplinary development; institutional support; agricultural production and infrastructure formations of the European type.